Situs Problematika Pariwisata Situs Kota Cina Medan: Indonesia - Lia, Zuliana; Nadia Resya Siregar; Elsarah Natasha Sitepu (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2022)
The research was conducted to find out the problems of Kota Cina Sites tourism as educational and cultural tourism. The technique used in this research is the technique of interview, observation, and documentation. Qualitative data whose sources consist of primary and secondary sources. The data collection technique is using purposive sampling technique, while the data analysis technique is in the form of qualitative descriptive data. The results of this study indicate a complex problem in Kota Cina Site tourism which includes three things, including (a) Community; (b) Government; and (3) Natural and Non-Natural Disasters. The problem is the lack of attention from the community and government in preserving and managing the Kota Cina Site to develop it as a historic site that has the potential for educational and cultural tourism. As well as sea tides that caused the Kota Cina site to experience sea intrusion and also the problem of conflict of interest. However, attention is still getting from the private sector, archaeologists, and academics